2019
DOI: 10.5455/javar.2019.f311
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of colistin resistant E. coli in poultry, house flies and pond water in Mymensingh, Bangladesh.

Abstract: Objective: Emergence of colistin-resistant Escherichia coli (CREC) has generated a sense of public alarm. The objective of this study was to detect the CREC and identification of the gene responsible for such resistance. Materials and Methods: A total of 150 samples comprising poultry cloacal swab, house flies ( Musca domestica ), and pond water were collected randomly from Mymensingh, Bangladesh and analyzed. Isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Based on the survey results, seven antibiotics were selected. In addition, two carbapenem antibiotics were included based on reports that indicated that E. coli could be resistant to carbapenems in poultry [31,50,59]. Guided by bird mortality rates and antibiotic use reports from the survey, five farms from two districts were selected for sample collection.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the survey results, seven antibiotics were selected. In addition, two carbapenem antibiotics were included based on reports that indicated that E. coli could be resistant to carbapenems in poultry [31,50,59]. Guided by bird mortality rates and antibiotic use reports from the survey, five farms from two districts were selected for sample collection.…”
Section: Methodsmentioning
confidence: 99%
“…The isolation of Salmonella from poultry was previously reported in Bangladesh, however, none of these studies focused on the molecular detection of resistance genes [23][24][25][26]. However, resistance genes were detected in Escherichia coli isolated from cloacal swabs of boiler chicks in Bangladesh [27,28]. Moreover, a study in Bangladesh, detected resistance genes in E. coli and Salmonella from dairy farms [29].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from many countries have detected drug resistance determinants in APEC [ 27 , 28 ]. In Bangladesh, previous studies have identified antibiotic-resistant E. coli from poultry [ 29 , 30 , 31 , 32 ]. These studies, however, did not focus on APEC and the associated virulence genes.…”
Section: Introductionmentioning
confidence: 99%